The Difference between Square Step Exercise and Balance Strategy Exercise Effects On The Change of Limb Muscle Strength and Balance in Elderly People - Sulfitra Sulfitra; Irfan Idris; Djohan Aras (UNIVERSITAS NEGERI MAKASSAR, 2022)
The aging process is something that will be experienced by every individual which will be accompanied by a decrease in various functions of the body including a decrease in balance and muscle strength it can increase the risk of falling in the elderly which can cause injury, fracture, and even death. This study aims to compare the effects of the Square step exercise to the Balance exercise strategy on changes in limb muscle strength and balance in the elderly. The design of this study is comparative analytic with a sample of 40 elderly people experiencing balance disorders and decreased limb muscle strength. The respondents were grouped into two. Each group consists of 20 respondents. The first group is that of respondents who were given Square step exercise treatment and the second group includes the respondents given the Balance exercise strategy. Based on the results of the paired t-test analysis, there was a significant effect on changes in balance and lower limb muscle strength with a value (p = 0.001) in the group treated with the Square step exercise. In the Balanced exercise strategy treatment group, there were also significant changes in balance and lower leg muscle strength (p = 0.001). The results of the independent t-test indicated a significant difference between the group of respondents who were given the Square step exercise and the group of respondents who were given the Balance exercise strategy that includes balance changes (p = 0.033) and changes in muscle strength. leg (p=0.027). In conclusion, the Balance exercise strategy is better in increasing limb muscle strength and balance in the elderly compared to the Square step exercise. Hence the Balance exercise strategy can be used as a reference in reducing the risk of falling in the elderly.